Technology Education in Elementary School Using the Example of 'Learning Robots' – Development and Evaluation of an In-Service Teacher Training Concept. - Janicki, Nicole; Tenberge, Claudia

Grade 6 Students’ Perception and Use of Data-Based Decision Trees - Podworny, Susanne; Fleischer, Yannik; Hüsing, Sven (Bridging the Gap: Empowering and Educating Today’s Learners in Statistics. Proceedings of the Eleventh International Conference on Teaching Statistics)
Decision-making processes are often based on data and data-driven machine learning methods in different areas such as recommender systems, medicine, criminalistics, etc. Well-informed citizens need at least a minimal understanding and critical reflection of corresponding data-driven machine learning methods. Decision trees are a method that can foster a preformal understanding of machine learning. We developed an exploratory teaching unit introducing decision trees in grade 6 along the question “How can Artificial Intelligence help us decide whether food is rather recommendable or not?” Students’ performances in an assessment task and self-assessment show that young learners can use a decision tree to classify new items and that they found the corresponding teaching unit informative.

Aktuelle Entwicklungen in der Lehrer:innenbildung für Inklusion: Herausforderungen – Konzepte – Perspektiven. Keynote an der Tagung: Lehrer:innenbildung für Inklusion – Hochschuldidaktische Konzepte und Perspektiven an der Pädagogischen Hochschule Heidelberg - Büker, Petra
September 2022

Als Sozialforscher*innen die eigene Schule evaluieren und mitgestalten: Kindersichten auf ein partizipatives Setting in der Grundschule - Büker, Petra; Hüpping, Birgit (Mitbestimmung von Kindern. Grundlagen für Unterricht, Schule und Hochschule)

Reflexion und Reflexivität im Kontext Grundschule. Perspektiven für Forschung, Lehrer:innenbildung und Praxis

Catalytic Properties of High Nitrogen Content Carbonaceous Materials - Lepre, Enrico; Rat, Sylvain; Cavedon, Cristian; Seeberger, Peter H.; Pieber, Bartholomäus; Antonietti, Markus; Lopez Salas, Nieves (Angewandte Chemie International Edition)
Keywords: General Chemistry; Catalysis

Mn(ii) sub-nanometric site stabilization in noble, N-doped carbonaceous materials for electrochemical CO2 reduction - Kossmann, Janina; Sánchez-Manjavacas, Maria Luz Ortiz; Brandt, Jessica; Heil, Tobias; Lopez Salas, Nieves; Albero, Josep (Chemical Communications)
The reported N-doped noble carbonaceous support provides strong stabilization of Mn( ii ) sub-nanometric active sites as well as a convenient coordination environment to produce CO, HCOOH and CH 3 COOH from electrochemical CO 2 reduction.
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; General Chemistry; Ceramics and Composites; Electronic; Optical and Magnetic Materials; Catalysis

Efficient ethanol electro-reforming on bimetallic anodes supported on adenine-based noble carbons: hydrogen production and value-added chemicals - Rodríguez-Gómez, Alberto; Lepre, Enrico; Dorado, Fernando; Sanchez-Silva, Luz; Lopez Salas, Nieves; de la Osa, Ana Raquel (Materials Today Energy)
Keywords: Energy Engineering and Power Technology; Fuel Technology; Nuclear Energy and Engineering; Materials Science (miscellaneous); Renewable Energy; Sustainability and the Environment

Constructing Interfacial Boron‐Nitrogen Moieties in Turbostratic Carbon for Electrochemical Hydrogen Peroxide Production - Tian, Zhihong; Zhang, Qingran; Thomsen, Lars; Gao, Nana; Pan, Jian; Daiyan, Rahman; Yun, Jimmy; Brandt, Jessica; Lopez Salas, Nieves; Lai, Feili; Li, Qiuye; Liu, Tianxi; et al. (Angewandte Chemie International Edition)
Keywords: General Chemistry; Catalysis

Overcoming Electron Transfer Efficiency Bottlenecks for Hydrogen Production in Highly Crystalline Carbon Nitride‐Based Materials - Teixeira, Ivo F.; Tarakina, Nadezda V.; Silva, Ingrid F.; Lopez Salas, Nieves; Savateev, Aleksandr; Antonietti, Markus (Advanced Sustainable Systems)
Keywords: General Environmental Science; Renewable Energy; Sustainability and the Environment